PENGARUH LATIHAN KELINCAHAN REAKSI TERHADAP KELINCAHAN STEEPING KUMITE PRA PEMULA PUTRA DOJO PADEPOKAN PERAWANG - Rika Fuspita; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this study is that the reactions agility is still lacking, it is seen from various tests and official matches and this is one of the factors causing defeat. This type of research is a type of experimental research to see the effects of this form of exercise. The purpose of this research is to see the effect of agility reacting exercise on agility steeping kumite pre starter of dojo Perawang pad. Population in this research is athletes Pre Pemula Putra Dojo Padepokan Perawang which amounted to 8 people. The sampling technique is by using total sampling, in which the total population is sampled. Technique of taking data obtained from pre-test and posttest. Instrument in this research using Test of Agility Reaction as tool to measure steeping agility skill. The analysis was performed using t-test. Based on the analysis and discussion of data, it can be concluded that there is a significant influence of reactor agility exercises on agility steeping kumite pre beginner children dojo Perawang as evidenced by Thitung of 7406 and Ttabel 1.860. Means Thitung> Table. At ɑ = 0.05 level.Keywords: Agility exercises reaction, agility steeping